The function of rhetorical devices in pleasantry of Baharestan Jami - یدالله شکری; عباس سعیدی (مطالعات زبانی و بلاغی)
Literal pleasantry is one of the manifestations of humor in classic literature which along with humor genre has come to appearance in critical literature due to the dominant atmosphere in the society of its time and the ineligibility for creating social humor and has achieved a special position for itself.